Effect of glucose and lysine supplementation on myogenic and adipogenic gene expression in muscle satellite cells isolated from Hanwoo with different genotypes of PLAG1: Implications for cell-based food production - Hyojin Kim; Sungkwon Park; Bosung Kim; Minji Kim; Tae Hyung Lee; Jia Yu; Il Soo Park; Sun Jin Hur; Xiang Zi Li; Seong Ho Choi (Current Research in Food Science)
Research on Hanwoo cattle has focused on the pleomorphic adenoma gene (PLAG) family, vital for traits like growth and carcass quality. Single nucleotide polymorphisms (SNPs) within this gene family profoundly impact economic traits. At the cellular level, energy and protein sources, notably glucose and lysine, crucially regulate muscle satellite cell (MSC) growth and differentiation.This study delved into how varied glucose and lysine levels affect gene expression patterns in Hanwoo MSC. MSC from 9 Hanwoo, aged 29–36 months, categorized into 3 PLAG1 genotypes (GG, GC, CC), were treated with six combinations of glucose (5.5 and 25 mM) and lysine (2, 4, and 8 mM). Analysis of myogenic and adipogenic genes linked to meat quality and quantity ensued.The GG genotype displayed superior dressed percentage, yield grade, and marbling score, hinting at genotype-associated carcass characteristic disparities. In cell culture, gene expression generally rose with lysine addition to high glucose in the GG group. Contrarily, significant differences across all treatments in the GC genotype suggested distinct responses. Significant effects of genotype, glucose, and lysine on cell proliferation-related gene expression were noted. Highest mRNA expression for MyoD, MyoG, and FASN occurred in the CC genotype, while Myf5 and Pax7 expression peaked in the GG genotype. Glucose significantly influenced Pax7 and FASN expression, while lysine positively impacted MyoD and MyoG genes. Notable interactions, especially in Genotype × Lysine, influenced MyoD, Myf5, and Pax7 expression, highlighting complex relationships in cell proliferation. Regarding cell differentiation, Pax7 expression was highest in PLAG1 GG type. High glucose prompted wider myotubes, while lower lysine concentrations slightly favored cell differentiation. Correspondingly, MyoG expression decreased with higher lysine levels.This study furnishes insights into lysine and glucose supplementation effects on bovine MSC proliferation and differentiation, considering PLAG1 genotype influence. It offers valuable data for beef production system establishment and optimizing cell-based food production.